Conditions for Negotiation of the General Agreement on Trade and Services ("GATS") in the World Trade Organization ("WTO") (Revista da Faculdade de Direito, Universidade de São Paulo, 2006)
This article tries to identify some of necessary conditions to the progress of negotiations of GATS in the WTO. The author states the maintenance of flexible structure of GATS, which allow Members to assume commitments to the objectives and their development public policies. It discusses some opening requests proposed through multilateral negotiations, like those made in relation to broadcast, telecommunication and computer services. It writes the importance of article VI.4 of GATS, which disposes about domestic regulation, and aim the maintenance of the space of Members to regulate their services sector. It highlights the need of creation of certain rules, like those related to subsides and emergency safeguards.